Solar shelter: Exploring architectural design input for industrially-crafted shading devices - Ulrich Pont; Sigrun Swoboda; Peter Schober (Acta Polytechnica CTU Proceedings, 2022)
European Cities are strongly affected by the Urban Heat Island effect and Climate change impacts in recent and future summer periods. As such, the integration of passive cooling strategies is of increasing importance for the overall AEC (Architecture-Engineering-Construction) domain. Amongst other strategies, one of the most prominent strategies is the timely deployment of shading devices. While the shading device constructions connected to the inside, interstitial position or exterior of transparent building envelope components is thus an important part of the building, little change can be observed in the principal design and technology of such shading elements. Moreover, target conflicts between shading device deployment and architectural appearance can be observed in European Cities. For instance, the ensemble protection of the Vienna City morphology was - for a long time - considered to be more important than potent shading devices.The present contribution presents the approach of an effort toward highly-esthetical, functional shading devices that provide - despite their architectural-design approach - a high degree of shading performance. Together with the window-building industry, four different shading device designs have been designed, developed and virtually tested. The design process was guided by critical reviews by domain experts and performance simulation efforts. We present the genesis of the four designs and their performance implications as a proof of concept that effective shading systems can be understood as part of the esthetics of a building and practical passive cooling device at the same time.